13x-203=6x-7

Simple and best practice solution for 13x-203=6x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13x-203=6x-7 equation:


Simplifying
13x + -203 = 6x + -7

Reorder the terms:
-203 + 13x = 6x + -7

Reorder the terms:
-203 + 13x = -7 + 6x

Solving
-203 + 13x = -7 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-203 + 13x + -6x = -7 + 6x + -6x

Combine like terms: 13x + -6x = 7x
-203 + 7x = -7 + 6x + -6x

Combine like terms: 6x + -6x = 0
-203 + 7x = -7 + 0
-203 + 7x = -7

Add '203' to each side of the equation.
-203 + 203 + 7x = -7 + 203

Combine like terms: -203 + 203 = 0
0 + 7x = -7 + 203
7x = -7 + 203

Combine like terms: -7 + 203 = 196
7x = 196

Divide each side by '7'.
x = 28

Simplifying
x = 28

See similar equations:

| 5+2t-2=6t+9-2t | | 10.4+3.2f=5f+4 | | 4x-6=4(x+1) | | 3(-9)+2= | | -6x-17=-125 | | -23+22=m-4 | | v-7.92=1.9 | | 31-(3x+5)=3(x+4)+x | | 10x-17=12x+21 | | -0.6x-0.3x+8=-1 | | 12x-5=7x+50 | | x-8.2=4.5 | | 9r-6r+6=6r+6-r | | -2w-4w-24=48 | | 736=4(x+18) | | 2y-15=85-3y | | 6r+4=26r+9 | | 9x+42+15x=4y-13 | | 5(-x)-5= | | 0.6x-1=0.5 | | -296=-8(-8x-3) | | (x+8)(2x+4)(3x-6)=0 | | 50x+50x=300 | | 5x+5-5= | | .05(2t-6)=.10(t+4)-.70 | | -4-3(t-5)= | | 2(x-6)=36 | | 8(z+8)= | | 25=45b | | -7+y=34 | | 4(x+2)+2=7x-3(x-2) | | -93=-1 |

Equations solver categories